Calcified carotid atherosclerotic plaque in panoramic radiographs in patients with Diabetes mellitus- A Retrospective Study - NIVETHA; M, ARVIND; S, ARVIND (The journal of contemporary issues in business and government, 2020)
Atherosclerosis is characterized by thickening and loss of elasticity of the arterial walls, associated with the presence of atheromatous plaques.It is associated with diabetes mellitus and leads to increased risk of stroke.The aim of this study is to determine the prevalence of atherosclerotic plaques in panoramic radiograph in patients with diabetes mellitus.A retrospective study was carried out in diabetic patients who took panoramic radiographs for routine dental examination visiting Radiology department.The data were obtained from analysing 86000 patients records between June 2019-March 2020.The data comprised of 220 diabetic patients who visited Radiology department.The collected data were entered into Excel sheet and subjected to statistical analysis using SPSS software.A chi square test was done between variables.Results showed that prevalence of atheroscleerotic plaque on panoramic radiographs in patients with diabetes mellitus was found to be 34.09% . Out of 34.09%, 61.11% had unilateral atherosclerotic plaque and 38.89% had bilateral atherosclerotic plaque.Statistically significant association was found between age and presence of atherosclerotic plaque (p-value:0.014).The present study concludes that presence of atherosclerotic plaque was found highly in female diabetic patients and patients under 40-60 age group.